IN SEARCH OF NETWORK MANAGEMENT PATTERNS IN TOURISM DEVELOPMENT POLICY: CASE OF SINGKAWANG MUNICIPALITY, WEST KALIMANTAN, INDONESIA - Ira Patriani; Ida Widianingsih; Arry Bairus; Heru Nurasa (Universitas Medan Area, 2018)
This paper discusses the network management process (interaction, dynamic, strategy) of tourism policy in decentralised Indonesia. The study was conducted at Singkawang Municipality, West Kalimantan, Indonesia as a resource rich region in the border of Indonesia and Malaysia. In understanding the interaction, dynamic and strategy of the development in the tourism sector, it is important to identify the patterns of network management. This research primarily utilizedthe network management strategy of Kickert, Klijn and Koppenjan (1999) who put emphasize on the interactions between development policy actors. By using a qualitative approach, the research found that in the context of tourism development, the interaction and dynamic patterns among policy actors are developed through linear individual cooperation. Within this pattern, the interaction amongst policy actors tend to involve certain individuals who have authority in controlling resources regardless ofwhich organizations they belonged to. In fact, this pattern is strongly based on family relationships or friendships found in both public and private domains. The research concludes that the strategies used in developing the tourism sector in Singkawang municipality should be developed based on facilitating strategic interaction, preventing the exclusion of strategic ideas, introduction of new strategic ideas, and furthering strategic reflections.